2019
DOI: 10.1182/blood.2019001113
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and phenotypes of JAK2 V617F and calreticulin mutations in a Danish general population

Abstract: The JAK2 V617F and calreticulin mutations (CALR) are frequent within myeloproliferative neoplasms (MPNs). JAK2 V617F has been detected in the general population, but no studies have previously investigated the CALR prevalence. Thus, we aimed to determine the CALR and JAK2 V617F population prevalence and assess the biochemical profile and lifestyle factors in mutation-positive individuals with and without MPN. 19 958 eligible participants, enrolled from 2010-2013, from the Danish General Suburban Population Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
150
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(160 citation statements)
references
References 67 publications
8
150
1
1
Order By: Relevance
“…using JAK2-V617F mutant-specific inhibitors. This rationale is further supported by the fact that JAK2-V617F clonal hematopoiesis is associated with an increased risk of cardiovascular disease 36 and venous thrombosis 45,46 and by the decades long time interval between JAK2-V617F acquisition and MPN development uncovered by our work.…”
Section: Discussionsupporting
confidence: 63%
“…using JAK2-V617F mutant-specific inhibitors. This rationale is further supported by the fact that JAK2-V617F clonal hematopoiesis is associated with an increased risk of cardiovascular disease 36 and venous thrombosis 45,46 and by the decades long time interval between JAK2-V617F acquisition and MPN development uncovered by our work.…”
Section: Discussionsupporting
confidence: 63%
“…Although the JAK2 V617F mutation is considered to be the major cause of MPN, it has been recently shown that JAK2 V617F positive neoplasms often develop in a background characterized by clonal hematopoiesis and other genetic alterations. Recently, different exome-analyses studies have identified the occurrence of age-related clonal hematopoiesis in healthy populations, to which the JAK2 V617F prevalence in the Danish population, close to 3%, could be ascribed [18]. By using highly sensitive methods, like ddPCR, we did not find a JAK2 V617F mutation in the control population, probably due to the low number of control samples used in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…The Danish General Suburban Population Study ( GESUS ) is a cross‐sectional general population study of 21 205 adults (participation rate 43%) from 2010 to 2013 (Bergholdt et al , ; Cordua et al , ). We included 11 083 healthy participants {mean age was 52 years [SD (s tandard deviation ): 12], 53·5% were women} with no cardiovascular disease or cancer.…”
Section: Methodsmentioning
confidence: 99%